The Analysis of Leontopodium leontopodioides (Willd.) Beauv. Chemical Composition by GC/MS and UPLC-Q-Orbitrap MS - Yuanyuan Chen; Yu Dong; Lin Song; Changxi Bai; Buhechaolu Wang; Chula Sa (International Journal of Analytical Chemistry)
Leontopodium leontopodioides (Willd.) Beauv. (L. leontopodioides.) has been used to treat lung diseases in traditional Chinese medicine (TCM). However, a systematic analysis of its chemical components has not been reported so far. In this study, UPLC-Q-Orbitrap MS and GC-MS were applied to investigate the chemical composition of the water extracts and essential oils of L. leontopodioides. UPLC-Q-Orbitrap MS adopts a heating electrospray ionization source, collecting primary and secondary mass spectrometry data in positive and negative ions, respectively, and uses Compound Discoverer 3.2 software to analyze the collected raw data. As a result, a total of 39 compounds were identified from their high-resolution mass spectra in both positive and negative ionization modes, including 13 flavonoids and their glycosides, 15 phenolic acids, 4 oligosaccharides and glycosides, 4 pentacyclic triterpenoids, and 3 other compounds. Among them, 18 chemical components have not been reported in L. leontopodioides. In the GC-MS section, two common organic solvents (n-hexane and diethyl ether) were used to extract essential oils, and the mass spectra were recorded at 70 eV (electron impact) and scanned in the range of 35∼450 m/z. Compounds were identified using NIST (version 2017), and the peak area normalization method was used to calculate their relative amounts. Finally, 17 components were identified in the volatile oil extracted with n-hexane, accounting for 80.38% of the total volatile oil, including monoterpenoids, phenylpropene, fatty acids, and aliphatic hydrocarbons. In the volatile oil extracted with diethyl ether, 16 components were identified, accounting for 73.50% of the total volatile oil, including phenylpropene, aliphatic hydrocarbons, monoterpenoids, fatty acids, and esters. This study was the first to conduct a comprehensive analysis of the chemical composition of the L. leontopodioides water extract and its essential oil, and a comprehensive chemical composition spectrum was constructed, to lay a foundation for its further pharmacodynamic material basis and quality evaluation.